(untitled) (International journal of artificial intelligence, 2026)
The developed classification of educational tasks aimed at developing linguistic and methodological competence is focused on the applied aspects of integrating neural network technologies into teaching practice. The key vector of the designed tasks is the modeling of the professional activity of a specialist facing research and didactic challenges.